Experiments and modeling of mechanism analysis of maize picking loss - Zhang, Zhen; Chi, Ruijuan; Du, Yuefeng; Pan, Xiang; Dong, Naixi; Xie, Bin (International Journal of Agricultural and Biological Engineering, 2021)
Maize picking is the main form of maize harvest in China. Maize picking loss accounts for a large proportion of the current maize harvest loss. An experimental study and theoretical analysis were built to explore the influencing factors and rules of maize picking loss. First, the boundary conditions, established by analyzing the mechanism of maize picking, determined the influences of maize picking loss. Then, single-factor experiments and a central composite design (CCD) method were used to determine the influence of various factors and their interactions on maize picking loss. Finally, the models of kernel loss and ear loss were set up to determine the optimal parameter combination of maize picking harvest. Field experiment verification was conducted. The results indicated that the optimal parameters of the maize picking harvest were the rotational speed of pulling rollers of 1120 r/min, operating speed of 1.94 m/s, the inclination of the header of 18° and clearance between the picking plates of 30 mm. By establishing these optimal parameters, the kernel loss rate was 0.065%, and the ear loss rate was 0%. The obtained experimental results and regression models could be used to predict the performance of the maize picking harvest, guide the adjustment of header working parameters, and provide a theoretical basis for reducing the mechanical loss of maize harvesting. Keywords: maize picking harvest, kernel loss rate, ear loss rate, maize picking platform, response surface analysis DOI: 10.25165/j.ijabe.20211401.5745 Citation: Zhang Z, Chi R J, Du Y F, Pan X, Dong N X, Xie B. Experiments and modeling of mechanism analysis of maize picking loss. Int J Agric & Biol Eng, 2021; 14(1): 11–19.